1. Jan 18, 2010

### Bear_B

1. The problem statement, all variables and given/known data

lim as h->0 of (f(x(sub 0)+h)-f(x(sub 0))/h

f(x)=3$$\sqrt{x}$$+2
x(sub 0)=9

2. Relevant equations

limit laws and factoring (my first post, not sure what I need to write here)

3. The attempt at a solution

=lim as h->0 of (f(9+h)-f(9)0/h
=lim as h->0 of (3$$\sqrt{9+h}$$+2-(3$$\sqrt{9}$$+2)/h
=lim as h->0 of (3$$\sqrt{9+h}$$+2-3$$\sqrt{9}$$-2)/h
=lim as h->0 of (3$$\sqrt{9+h}$$-9)/h

I am stuck here. I know I need to somehow move h out of the denominator(most likely by factoring) but am stuck on how to deal with the radical in the numerator.
1. The problem statement, all variables and given/known data

2. Relevant equations

3. The attempt at a solution

2. Jan 18, 2010

### vela

Staff Emeritus
Rationalize the numerator by multiplying both the top and bottom by $$3\sqrt{9+h}+9$$.

3. Jan 18, 2010

### Bear_B

Ok, so I multiplied the numerator and denominator by 3$$\sqrt{9+h}$$+9 and am still having problems, here's what I got:

=lim as h->0 of (3$$\sqrt{9+h}$$-9)/h * (3$$\sqrt{9+h}$$+9)/(3$$\sqrt{9+h}$$+9)

=lim as h->0 of (9(9+h)+27$$\sqrt{9+h}$$-27$$\sqrt{9+h}$$-81)/(3h$$\sqrt{9+h}$$+9h)

=lim as h->0 of (81+h-81)/(3h$$\sqrt{9+h}$$+9h)

=lim as h->0 of h/(3h$$\sqrt{9+h}$$+9h)

ok, I am stuck here again and don't see what I did wrong or what I still need to do

4. Jan 18, 2010

### Bohrok

You didn't distribute the 9 in the second line of your work; that will give you 9h in the numerator. Also, don't distribute the h in the denominator.
This is what you should have now without distributing it:

$$\lim_{h\rightarrow 0} \frac{9h}{h(3\sqrt{9 + h} + 9)}$$

The h's cancel and then you can let h=0 in the expression.

Last edited: Jan 18, 2010
5. Jan 18, 2010

### Bear_B

Thanks for the help vela, you got me on the right track, and thanks Bohrok, you caught my mistake. I started over and worked it out and got the right answer.